Advanced Synthetic Aperture Radar Based on Digital Beamforming and Waveform Diversity - Krieger, Gerhard; Gebert, Nicolas; Younis, Marwan; Moreira, Alberto (IEEE Radar Conference (RadarCon), 2008)
This paper introduces innovative SAR system concepts for the acquisition of high resolution radar images with wide swath coverage from spaceborne platforms. The new concepts rely on the combination of advanced multi-channel SAR front-end architectures with novel operational modes. The architectures differ regarding their implementation complexity and it is shown that even a low number of channels is already well suited to significantly improve the imaging performance and to overcome fundamental limitations inherent to classical SAR systems. The more advanced concepts employ a multidimensional encoding of the transmitted waveforms to further improve the performance and to enable a new class of hybrid SAR imaging modes that are well suited to satisfy hitherto incompatible user requirements for frequent monitoring and detailed mapping. Implementation specific issues will be discussed and examples demonstrate the potential of the new techniques for different remote sensing applications. © 2008 IEEE.
DLR Import::2019-04-03
Keywords: Digital Beamforming; High-Resolution Wide-Swath (HRWS) SAR Imaging.; MIMO Radar; Synthetic Aperture Radar (SAR); Waveform Diversity